An Improved Playfair Encryption Technique Using Fibonacci Series Generated Secret Key - Vasim Ahamad, Mohd; Urrahman Siddiqui, Misbah; Masroor, Maria; Fatima, Urooj (International Journal of Engineering and Technology, 2018)
With the technology advancements and easy availability of internet, every day millions of users share information electronically through emails, file sharing, e-commerce, etc. As, internet is highly vulnerable to various attacks, sending sensitive information over the Internet may be dangerous. One of the ways to protect the sensitive Information is using the cryptographic techniques. So, while sharing sensitive information over the Internet, it should be sent in encrypted form to prevent the access by unauthorized person. Encryption can be defined as the process of transforming information in such a manner that only authorized person can understand the shared information. In this paper, we have taken Playfair encryption algorithm for encryption and modified it by using Fibonacci series. Fibonacci series is used to generate a random key, which is used for encrypting the message in Playfair encryption algorithm. Using Fibonacci numbers and generating random keys provide significant security to shared information.